ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER PADA PT GLOBAL DIGITAL NIAGA TBK (BELI) - Cahyani, Mutiara Suci; Murwanti, Sri (JURNAL ILMIAH EDUNOMIKA, 2024)
This research examines the problem of comparing financial performance before and after the merger at the company PT Global Digital Niaga Tbk. This type of research uses descriptive comparative research using a quantitative method approach and secondary data in the form of financial reports at PT Global Digital Niaga Tbk with a period of 2 years before and after the merger. Data obtained from financial reports from the official website of PT Global Digital Niaga Tbk. This research shows that the financial performance of the company PT Global Digital Niaga Tbk is based on financial ratios, namely the ratio of rate of return on assets (ROA), rate of return on equity (ROE), current ratio (CR), and debt to equity (DER). significant does not occur before or after the merger.